Pearls analysis to assess the health level of Hati Amboina service office (KP) Saumlaki Cooperative Credit Union (CU) - Maria J.F Esomar; Baretha Meisar Titioka (STIE Binaniaga, 2021)
Performance measurement of Credit Union is important to do in order to improve and at the same time becomes a way of evaluating achievement in specific periods. It will show level of success of operational activities conducted and create foundation of developing strategy in the coming days. To get a clear view of a financial report, there has to be a financial performance measurement of Credit Union of Hati Amboina KP Saumlaki through financial rasio analysis named PEARLS which is identified as P (Protection), E (Effective Financial Structure), A (Asset Quality), R (Rate of Return & Cost), L (Liquidity), S (Signs of Growth). This research aims to know how healthy the finance of Credit Union of Hati Amboina KP Saumlaki from year of 2017 to 2019 using PEARLS Rasios. The research shows that Credit Union of Hati Amboina KP Saumlaki is good enough in financial health which described in many variables suit PEARLS Rasios. Overall PEARLS Rasios explains that financial condition of Credit Union Hati Amboina KP Saumlaki is healthy enough. To some rasios that fulfill no standard ideally, the Credit Union needs to find proper strategy to raise its financial performance. Keywords: Credit Unions, PEARLS,performing operations